TINDAKAN KEKERASAN TERHADAP ANAK DALAM TAFSIR PENDIDIKAN - Zuman Malaka (Tarunaedu: Journal of Education and Learning, 2023)
Violence against children is not something new, in fact it is an endless phenomenon. This phenomenon can occur anywhere and at any time. Often we see acts of violence that befall children, whether physically, psychologically, sexually, economically, and so on. In the Al-Qur'an, Surah Al Imran, verse 159, it is explained that as a parent you must be gentle towards your child and provide guidance to your child with love and be able to provide direction to understand what your child can and cannot do. This is done to avoid acts of violence against children.